Coding with Anna and Elsa : a Frozen guide to Blockly - Prottsman, Kiki (Lerner Publications, 2019)
Discover coding with Blockly with the help of friends from Frozen. Step-by-step instructions guide readers through exercises to teach sequencing, debugging, and more. Readers can try out the skills they learn in a code.org companion site--